Analisis Kritis Anggaran Pertahanan: Studi Literatur Tentang Metode Pengelolaan dan Evaluasi - Sianipar, Leo; Saputro, Guntur Eko; Sundari, Sri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Defense budget is an essential component in a country's defense strategy. The selection of effective methods in managing and evaluating defense budgets can have a significant impact on national defense capabilities. Therefore, this study aims to critically analyze the methods of managing and evaluating defense budgets through relevant literature studies. The method used in this research is literature review, involving the collection and analysis of journals, books, government reports, and other relevant publications. This research involves an in-depth examination of the methods of managing and evaluating defense budgets that have been implemented by countries across the globe. The analysis results indicate that there is significant variation in the approaches to managing and evaluating defense budgets in different countries. Commonly used methods include top-down and bottom-up approaches, cost-benefit analysis, risk analysis, and strategic planning techniques. Furthermore, this research also identifies the challenges faced by countries in managing and evaluating defense budgets, such as political complexity, strategic uncertainty, and resource limitations. This study provides valuable insights into the methods that can be applied in managing and evaluating defense budgets. In the context of national defense planning, a profound understanding of these various methods can assist countries in optimizing their resource allocation, enhancing the efficiency and effectiveness of defense budget management, and strengthening national defense capabilities. Keywords: Defense Budget, Budget Management, Budget Evaluation, Defense Strategy, National Defense Planning.